Audit Energi Listrik Dan Analisa Peluang Penghematan Konsumsi Energi Listrik di Hotel Gatsu Indah Denpasar - Galang B. P.,, Gusti Ngurah Made; Wijaya Kusuma, I.G.B.; Tenaya, I.G.N. Putu (Teknik Desain Mekanika, 2021)
Abstract The use of electrical energy in the Hotel industry is more widely used in lighting and cooling systems. Inaccurate selection of the type and capacity of air conditioning cooling will result in a waste of electrical energy. This research is intended to calculate the cooling load on the Gatsu Indah Hotel room in order to find out how much electricity is wasted, as well as to increase the efficiency of the use of electrical energy. This study uses data collection methods by observation and interviews. Furthermore, data processing is carried out, namely: calculating the value of cooling load, OTTV, and IKE. After getting the results, it is followed by an analysis to get a conclusion. It can be concluded that the average cooling load in the Gatsu Indah Hotel room is 1224.1 W and the average OTTV value is 59.76 W / , when compared to the standard, namely 35 W / m2 This value is a fairly large category. The average value of the IKE Hotel Gatsu Indah throughout 2019 is 8.76 kWh / / month. when compared to air-conditioned buildings, the level of efficiency of the Gatsu Indah Hotel building is in the Efficient category because it does not exceed 12.08 kWh / / month. Keywords: Electrical energy audit, cooling load, OTTV